Back pain as the presenting symptom of generalised tetanus. Issue 1 (20th December 2006) - Simpson, J; Inglis, A; Gordon, M W G
Abstract : Back pain is a common presenting symptom in emergency departments and primary care across the UK. The extensive differential diagnosis includes mechanical, infective, thoracic, abdominal and vascular causes. This case report describes a patient who presented with lower back pain with a rare diagnosis, which is becoming more common in certain population groups, and emphasises the importance of clinical skills and insuring adequate tetanus prophylaxis.